RESPON PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) DI PERSEMAIAN PADA PEMBERIAN PUPUK HAYATI DAN KIMIA - Laswi Irmayanti; Mira Mariati; Salam Salam; Rusli Buamona (EnviroScienteae, 2019)
The objectives of this research were to determine the effect of chemical and biological fertilizers on the growth of red Jabon (Anthocephalus macrophyllus (Roxb.) Havil) seedlings in the nursery. This research was conducted at the Tembal Lestari nursery, South Halmahera Regency, North Maluku Province. The results of this research showed that giving a combination of biological and chemical fertilizers has a significant effect on the increase in height, diameter, and number of leaves of red jabon seedlings